Metropolitan dynamics and mobility times. Metropolitan region of Barcelona as example - Carme Miralles-Guasch (Anales de Geografía de la Universidad Complutense, 2011)
Metropolitan areas have been studies from the perspective of the spatial relationships mapped out by work commutes. This article attempts to complement this single-function view of reality of metropolitan life by presenting everyday journeys as activities that structure territories from the perspective of all travel-related motives, both work related and for personal reasons. In addition, travel time is a variable which is related to the uses of time spent on other activities. It is seen as a social value with its corresponding complementary and contradictory aspects to the extent that reconciling time also means reconciling metropolitan spaces. Using the Metropolitan Region of Barcelona (MRB) as an example, this article analyses metropolitan dynamics from the perspective of mobility times and from these gives an outline of everyday activities linked to spatial distance and mechanical means of transport, and also their everyday functions in proximity spaces, in the intensification of the neighbourhood and in the non-mechanical means of transport their principal characteristics.